Indigenous Rights and Interests in a Changing Arctic Ocean: Canadian and Russian Experiences and Challenges - Sharapova, Anna; Seck, Sara; MacLeod, Sarah; Koubrak, Olga (Arctic Review on Law and Politics, 2022)
The Arctic has been home to Indigenous peoples since long before the international legal system of sovereign states came into existence. International law has increasingly recognized the rights of Indigenous peoples, who also have status as Permanent Participants in the Arctic Council. In northern Canada, the majority of those who live in the Arctic are recognized as Indigenous. However, in northern Russia, a much smaller percentage of the population is identified as Indigenous, as legal recognition is only accorded to groups with a small population size. This article will compare Russian and Canadian approaches to recognition of Indigenous peoples and Indigenous rights in the Arctic with attention to the implications for Arctic Ocean governance. The article first introduces international legal instruments of importance to Indigenous peoples and their rights in the Arctic. Then it considers the domestic legal and policy frameworks that define Indigenous rights and interests in Russia and Canada. Despite both states being members of the Arctic Council and parties to the United Nations Convention on the Law of the Sea, there are many differences in their treatment of Indigenous peoples with implications for Arctic Ocean governance.